2015
DOI: 10.1007/s11738-015-1936-2
|View full text |Cite
|
Sign up to set email alerts
|

Protein complex and proteomic profile in the roots of Oryza sativa L. in response to cadmium toxicity

Abstract: Cadmium (Cd), a non-essential and toxic heavy metal element, is extremely harmful for rice growth, food safety and even public health. In this paper, two rice varieties, Shanyou 63 (Tolerant to Cd stress) and Nipponbare (Susceptible to Cd stress), were employed as materials to investigate the protein expression and protein-protein interaction in rice in response to different stages of Cd stress. The result showed that Cd accumulated in the root of both rice cultivars, but the Cd content in the root of Shanyou … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
1
0
0
Order By: Relevance
“…KEGG metabolic pathway analysis indicated that the DEPs of TGY were enriched in alpha linolenic acid, GSH, and phenylalanine metabolisms; plant–pathogen interactions; oxidative phosphorylation; and flavonoid biosynthesis, while those of SX were enriched in the biosynthesis of benzene propane, flavonoid, and single terpenoid and metabolic pathways of phenylalanine, starch, and sucrose. This is similar to the differential protein enrichment pathways in response to cadmium stress in cadmium-resistant and cadmium-sensitive rice varieties studied by Lin et al [ 23 ] and the enrichment pathway in response to copper stress in rice leaves studied by Hajduch et al [ 24 ]. Abnormal expression of antioxidant defensive proteins occurs during photosynthesis, thereby improving plant resistance.…”
Section: Discussionsupporting
confidence: 85%
“…KEGG metabolic pathway analysis indicated that the DEPs of TGY were enriched in alpha linolenic acid, GSH, and phenylalanine metabolisms; plant–pathogen interactions; oxidative phosphorylation; and flavonoid biosynthesis, while those of SX were enriched in the biosynthesis of benzene propane, flavonoid, and single terpenoid and metabolic pathways of phenylalanine, starch, and sucrose. This is similar to the differential protein enrichment pathways in response to cadmium stress in cadmium-resistant and cadmium-sensitive rice varieties studied by Lin et al [ 23 ] and the enrichment pathway in response to copper stress in rice leaves studied by Hajduch et al [ 24 ]. Abnormal expression of antioxidant defensive proteins occurs during photosynthesis, thereby improving plant resistance.…”
Section: Discussionsupporting
confidence: 85%